SOSIALISASI MAKANAN SEHAT DAN BERGIZI BAGI GURU-GURU SMP TERAMIA YAYASAN TUNAS BARU TIBAN BARU-SEKUPANG - Frangky Silitonga; Tri Muntia Yusri; Widyo Wicaksono; Kintan Sabrina; Heri Nuryanto; Karium Jackson M Nainggolan; Rullyan Syah Lubis; Novelia Abareles (ASOSIASI IDEBAHASA KEPRI, 2026)
The community service activity conducted by lecturers and students of Batam Tourism Polytechnic entitled “Healthy and Nutritious Food Socialization for Teachers of SMP Teramia, Tunas Baru Tiban Baru Foundation–Sekupang” aimed to enhance teachers’ understanding of the importance of healthy and nutritious eating patterns in supporting health, work productivity, and quality of life. The activity was carried out through socialization methods, delivery of educational materials, interactive discussions, and the provision of healthy menu examples tailored to daily nutritional needs. The materials presented included the introduction of balanced nutrition concepts, the selection of healthy food ingredients, the importance of consuming vegetables and fruits, reducing foods high in sugar, salt, and fat, as well as the implementation of healthy lifestyles within school and family environments. Through this activity, teachers are expected to become health education agents for students and the surrounding community. This community service activity also represents the implementation of the tridharma of higher education, particularly in community empowerment through health education and increasing awareness of the importance of healthy eating habits. Collaboration between lecturers and students is expected to strengthen the relationship between higher education institutions and the community while providing sustainable positive impacts on the educational environment.